KONTESTASI 2024 DAN PERAN NILAI-NILAI PANCASILA - Akhmad Gafuri (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Indonesia is a sovereign country that manages and serves all levels of society, as well as electing leaders who represent the people to implement and supervise the running of the government. Elections and Regional Head Elections are a means of implementing people's sovereignty in democracy. The contest to elect potential leaders in 2024 is entering a new era where national events will be held simultaneously. The 2024 contest is the starting point for implementing a democratic party that will involve all resources, both human resources and financial resources, which are expected to run effectively and efficiently. This is in line with the mandate of the fourth principle of Pancasila. The involvement of Indonesian Human Resources is very necessary both as Election Organizers, Election Participants and Election Voters, for the success of this National Agenda, Election Organizers, Election Participants and Voters should pay attention to and instill the values of Pancasila for the success of the 2024 Contest.